ANALYSIS OF THE CORN TRADING CHAIN AND MARGIN IN OGAN KOMERING ULU REGENCY - Efriliana Yusnita; Rini Efrianti; Fifian Permata Sari Fifian; Anggi Fatmayati; Dadang Kurnia (Bajang Institute, 2022)
This study aims to analyze the banana trading chain and margin in Jayapura District, East OKU Regency, South Sumatra Province. The research was carried out deliberately considering that Jayapura District, East OKU District is the center of bananas in East OKU District. The research was carried out in March 2022. The research method used was a survey method and the sampling method used was a simple random method. The analytical tool used in processing research data is a mathematical method with a margin formula to calculate marketing margin and marketing channel efficiency. Discussion of research results is carried out by descriptive analysis. The results showed that there were 3 banana trading channels in the research location, the processed data showed that the margin for trading at agents was 800 rupiahs and at 2000 rupiahs at retailers. The results also show that the most efficient trade system channel is channel 3 with an efficiency value of 1 percent.